The Role Of The Inspectorate In The Implementation OF Regional Autonomic Supervision In The Province Of North Sumatera View From A State Administrative Law Perspetive - Viza Vadilla (Journal of Law Science, 2020)
Inspectorate is an element of supervising the development and administration of provincial, district and city government which has the task of supervising the implementation of government affairs in the provinces, districts and cities. The problems raised in this thesis are: What is the position and role of the Inspectorate in the implementation of regional autonomy in North Sumatra Province. And the extent to which the Inspectorate can perform its role as a supervisory agency after the implementation of regional autonomy in North Sumatra Province. This research uses normative research methods, using library research and field research. The conclusion is: The Inspectorate of North Sumatra Province is located under the North Sumatra Provincial Government, in line with other agencies and services under the auspices of the North Sumatra Provincial Government which is responsible to the Governor through the Regional Secretary. The results of the examination of cases handled, especially in follow-up supervision, where before the implementation of regional autonomy the bureaucracy was complicated and lengthy and took a long time. However, after the implementation of regional autonomy, it is sufficient for the Governor to complete a Governor's Decree, except in cases where there are indications of criminal or civil acts that require the intervention of a third party. Factors supporting the implementation and functional supervision carried out by the Inspectorate of North Sumatra Province after the issuance of Law no. For this reason, it is recommended to the Inspectorate of North Sumatra Province to supervise the performance of the Regional Government of North Sumatra Province and its staff to be carried out by the Provincial Inspectorate. It is hoped that the Governor of North Sumatra will be transparent in responding to and forwarding cases found by the Inspectorate of North Sumatra Province and can provide a more adequate budget.